1965
DOI: 10.1113/jphysiol.1965.sp007624
|View full text |Cite
|
Sign up to set email alerts
|

Factors responsible for the stimulation of the adrenal medulla during asphyxia in the foetal lamb

Abstract: Previous investigations on the release of catecholamines from the adrenal medulla of the foetal lamb during asphyxia showed that certain characteristic changes occurred during the development of the foetus (Comline & Silver, 1961). From relatively early in pregnancy, 80-90 days (full term 147 days), the adrenal medulla appeared to react directly to asphyxia with a secretion which contained a high proportion of noradrenaline. This response remained unaffected by section of the splanchnic nerves, destruction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
1

Year Published

1969
1969
2002
2002

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(71 citation statements)
references
References 20 publications
5
65
1
Order By: Relevance
“…Animal experiments have shown that the tcpO 2 varies from the arterial pO 2 after recurrent hypoxic episodes. It appears that vasoconstriction of cutaneous vessels due to increased release of NE during hypoxia may be responsible for the observed tc-art pO 2 -d [6,7,16,17]. The heating element of the electrode obviously is not always capable of maintaining optimal cutaneous blood flow.…”
Section: Catecholamine Extraction By the Placentamentioning
confidence: 99%
See 1 more Smart Citation
“…Animal experiments have shown that the tcpO 2 varies from the arterial pO 2 after recurrent hypoxic episodes. It appears that vasoconstriction of cutaneous vessels due to increased release of NE during hypoxia may be responsible for the observed tc-art pO 2 -d [6,7,16,17]. The heating element of the electrode obviously is not always capable of maintaining optimal cutaneous blood flow.…”
Section: Catecholamine Extraction By the Placentamentioning
confidence: 99%
“…Investigations performed in animal experiments [6,7,16,17,19] as well as in man [2,3,9,10,18,20,25] suggest that fetal hypoxia is associated with an increase in circulating catecholamines due to sympathoadrenal stimulation. The correlation between catecholamines and cardiovascular, respiratory, and metabolic changes as determined during intrapartum fetal monitoring by means of cardiotocography (CTG), fetal blood gas analysis, and measurement of the transcutaneous partial oxygen tension (tcpC^) has not yet been exhaustively investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In fetal sheep (4,5,27) and neonatal rats (29), at least two mechanisms mediating catecholamine release in response to hypoxemia have been described. First, before functional innervation of the adrenal glands, hypoxemia may stimulate chromaffin cells directly to promote catecholamine release into the circulation.…”
mentioning
confidence: 99%
“…There is, however, a curvilinear relationship, so that the increment of fetal P Oa values for any given change of maternal P Oa will be less the higher the maternal P Oa . This type of relationship has been demonstrated in humans by RORKE et al [10], and in sheep by COMLINE et al [4]. Thus, the fetus appears to be protected from high levels of P O(l [2].…”
Section: Discussionmentioning
confidence: 71%
“…RORKE et al [10] in humans and several investigators using animals [5,4,1] have demonstrated that an increase of maternal oxygen tension causes only a disproportionately small increase of fetal oxygen tension. Such an effect might be explained by the fact that the placental venous P Oz increases only moderately and thus that the pressure head for oxygen diffusion is not elevated in proportion to maternal arterial P O2 .…”
Section: Introductionmentioning
confidence: 99%